The enigmatic Dacochile microsoma Poinar & Brown: Tanyderidae or Bruchomyiinae? - Poinar, George; Brown, Alex E. (Zootaxa, 2006)
An examination of character states in a second Burmese amber specimen of Dacochile microsoma Poinar & Brown from the type locality confirms the original placement of this species in the family Tanyderidae and not the Bruchomyiinae, as proposed by Woodley (2005). Of special interest are a row of heavily sclerotized processes shaped like rose thorns and positioned on the inside of the hind tibiae and first two tarsal segments. These processes, which point upward towards the body, suggest that at least the females of Dacochile supported themselves from vegetation by their hind legs, similar to the behavior of some present-day tanyderids.